2010
DOI: 10.1038/modpathol.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid sarcoma expresses epidermal growth factor receptor but gene amplification and kinase domain mutations are rare

Abstract: Epithelioid sarcoma is a rare, malignant, soft tissue neoplasm that can be classified into proximal, distal and fibroma-like subtypes. Regardless of subtype, epithelioid sarcoma often shows morphologic and immunophenotypic evidence of epithelial differentiation. Current therapeutic strategies include surgical resection, amputation, radiation or chemotherapy, although the overall prognosis remains poor. The epidermal growth factor receptor (EGFR) is a novel therapeutic target in carcinomas. In some carcinomas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…We have previously reported that in a cohort of 46 consecutive STS patients, 78% demonstrated positive expression of total EGFR [4]. This finding is consistent with other series in STS with a mean of 68% (range 60–77%) [5,6,7,8,9]. In a large Japanese study, total EGFR expression was significantly associated with histologic grade, but was not an independent prognostic factor of survival [5].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…We have previously reported that in a cohort of 46 consecutive STS patients, 78% demonstrated positive expression of total EGFR [4]. This finding is consistent with other series in STS with a mean of 68% (range 60–77%) [5,6,7,8,9]. In a large Japanese study, total EGFR expression was significantly associated with histologic grade, but was not an independent prognostic factor of survival [5].…”
Section: Introductionsupporting
confidence: 81%
“…Those who respond may have prolonged benefit but treatments typically do not result in a cure. In STS, we and others have provided evidence that the EGFR pathway may be a potential therapeutic target [3,4,5,6,7,8,9,10]. However, there have been very few, if any, informative clinical trials or objective radiologic responses to EGFR inhibition [16].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to evaluating the potential utility of EGFR as an ES therapeutic target we sought to expand previous observations of enhanced EGFR expression in this STS histological subtype (13). A pre-constructed TMA containing human ES specimens retrieved from 27 patients was used for immunohistochemical analysis (Fig 1A and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…First, a recent observation (13) identifying EGFR over-expression as commonly occurring in ES was validated, and was further expanded to demonstrate receptor activation in human ES samples. Moreover, a role for EGFR activation in supporting the malignant phenotype of ES was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation